Analisa Pengaruh Parameter Injection Moulding pada Produk Head Travel Kit Terhadap Cycle Time dan Netto Menggunakan Metode Response Surface - Yoga Karunia Perdana; Endang Pudji Purwanti; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Injection molding is a machining process that can form plastic-based objects in bulk and quickly. Some of the problems encountered in injection molding machines are long cycle times. This hampers the production rate. Several parameters to be analyzed for cycle time and net are injection speed, injection pressure, and holding pressure. Optimization of values for injection speed, injection pressure, and holding time is done to get the fastest cycle time and the lightest net product. The analysis process in this study uses the Response Surface method. The experimental design used was Box-Behnken with ANAVA to analyze the data. From the research conducted, it can be concluded that the injection speed parameter is a parameter that has a strong influence on cycle time, this is evidenced by the value of the injection speed tcount greater than the t table. Meanwhile, of the three parameters studied, individually did not affect the net response. The configuration parameters that produce the optimal value are the injection speed of 25 m / s, the injection pressure of 1586.8687 bar / kN, and the holding pressure of 1000 bar / kN. From this configuration, the cycle time value is 41.92 seconds and a net value is 4.739 grams.